Challenges and Strategies of Laboratory Diagnosis for Newly Emerging Influenza Viruses in Taiwan: A Decade after SARS. (28th July 2015) - Lin, Jih-Hui; Wu, Ho-Sheng
Abstract : Since the first case of severe acute respiratory syndrome (SARS) in Taiwan was identified in March 2003, viral respiratory infections, in particular the influenza virus, have become a national public health concern. Taiwan would face a serious threat of public health problems if another SARS epidemic overlapped with a flu outbreak. After SARS, the Taiwan Centers for Disease Control accelerated and strengthened domestic research on influenza and expanded the exchange of information with international counterparts. The capacity of influenza A to cross species barriers presents a potential threat to human health. Given the mutations of avian flu viruses such as H7N9, H6N1, and H10N8, all countries, including Taiwan, must equip themselves to face a possible epidemic or pandemic. Such preparedness requires global collaboration.